2020
DOI: 10.2169/internalmedicine.3865-19
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Effective Steroid Treatment of Three Patients with Allergy-related Jackhammer Esophagus

Abstract: We experienced marked efficacy with steroid treatment of three patients with jackhammer esophagus (JHE). An esophageal biopsy revealed eosinophilic esophagitis (EoE) in two patients. One of the patients without EoE had eosinophilia and an increased serum immunoglobulin E level, and endoscopic ultrasonography revealed thickening of the esophageal muscularis propria. Esophageal manometry was used to diagnose all cases of JHE. Treatment consisted of steroid administration, which improved the symptoms and resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…In many of these cases, eosinophilic myositis is detected by muscle layer biopsy during POEM [ 6 , 7 , 19 ]. Furthermore, from the therapeutic perspective, treatment with steroids has been successfully utilized in these patients [ 18 , 20 ]. In the present study, we found eosinophilic infiltration (i.e., > 15 eosinophils/high power field) in 12 of the 58 patients (21%) with JE who underwent esophageal mucosal biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…In many of these cases, eosinophilic myositis is detected by muscle layer biopsy during POEM [ 6 , 7 , 19 ]. Furthermore, from the therapeutic perspective, treatment with steroids has been successfully utilized in these patients [ 18 , 20 ]. In the present study, we found eosinophilic infiltration (i.e., > 15 eosinophils/high power field) in 12 of the 58 patients (21%) with JE who underwent esophageal mucosal biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in this group report normalization of IEM in response to pharmacological therapy in a proportion of patients with EoE, suggesting that reducing inflammation can improve or normalize motility abnormalities. 23,25,30,46,58,61,66 Eosinophils directly affect esophageal epithelial cells, with basal zone hyperplasia appearing to occur more markedly in EoE than in other types of esophagitis including GORD. 76 Furthermore, these changes can persist even when mucosal eosinophil count is reduced, suggesting ongoing disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, concomitant hypertrophy seen on EUS or CT has also been described in cases of muscularis propria eosinophilia. 22,25,[94][95][96][97] Degranulation of eosinophils releases substances that can influence smooth muscle function, particularly transforming growth factor beta 1 secreted by both eosinophils and mast cells, which has been demonstrated to cause smooth muscle contractions in vitro. 98 In addition, neuroactive substances including major basic protein, released as a result of degranulation of eosinophils, may influence neural function and thus disrupt normal motility patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the assessment of this process and monitoring of treatment related to the duration of steroid therapy, it seems crucial to use EUS and taking biopsies from deeper layers in a targeted manner [ 23 ]. Japanese researchers have also shown that esophageal motility disorders such as diffuse esophageal spasm, corkscrew esophagus and even esophageal achalasia can be related to EoE, and that an effective treatment can be managed according to EoE treatment standards, often without the need for surgical intervention [ 24 ]. These diseases although typical for adults can occur at any age, and EUS is well suited for diagnostic tools in addition to high-resolution manometry.…”
Section: Endoscopic Ultrasonography In Children With Eosinophilic Esophagitismentioning
confidence: 99%